Intumescent fire-retardant coating, preparation method and application thereof

CN118834574BActive Publication Date: 2026-11-03INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310444830.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-24
Publication Date
2026-11-03
Estimated Expiration
2043-04-24

AI Technical Summary

Technical Problem

Existing intumescent fire retardant coatings have discontinuous intumescent layers and insufficient mechanical strength, which makes them prone to falling off in high-temperature flames and unable to effectively insulate and protect steel.

Method used

By using silicone-modified acrylic emulsion, ceramic catalyst, and inorganic ceramic-forming functional filler, a dense carbon layer and a high-strength ceramic molecular-level composite structure are formed through in-situ catalysis, thereby enhancing the mechanical strength and thermal insulation performance of the coating.

Benefits of technology

The formation of a dense carbon layer and ceramic structure in a high-temperature flame improves the mechanical strength and thermal insulation properties of the expansion layer, prevents it from falling off, and enhances the fire protection of the steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004195214730000031
    Figure BDA0004195214730000031
  • Figure BDA0004195214730000041
    Figure BDA0004195214730000041
Patent Text Reader

Abstract

The present application relates to a kind of intumescent fire retardant coating and its preparation method and application, the intumescent fire retardant coating includes organic silicon modified acrylic emulsion, ceramic catalyst, inorganic porcelain function filler and intumescent fire retardant filler;The organic silicon modified acrylic emulsion includes the main body resin with core-shell structure;The raw material of the core layer of the main body resin includes acrylic monomer, styrene and acrylate silicone oil;The raw material of the shell layer of the main body resin includes acrylic monomer and styrene.The coating formed by the intumescent fire retardant coating described in the present application overcomes the problem that the expansion layer is discontinuous and the expansion effect is reduced due to physical doping inorganic particles, and then the mechanical strength of expansion layer is enhanced, and the effect of enhancing heat insulation protection is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fire-retardant coating technology, and in particular to an intumescent fire-retardant coating, its preparation method, and its application. Background Technology

[0002] Steel structures are widely used as an important building material in high-rise buildings, industrial plants, airports, and other applications. However, steel is not a fire-resistant material. When a building catches fire, the temperature of the steel exceeds 500°C, at which point it begins to soften and lose its original strength. Intumescent fire-retardant coatings form a protective layer on the steel surface. When a fire occurs, the coating undergoes acidification, vaporization, and carbonization, forming a heat-insulating expansion layer that protects the steel from flame damage.

[0003] CN108410352A discloses a water-based thin-film fireproof coating for steel structures, fireproof putty, and their preparation method. The disclosed fireproof coating includes fireproof putty and fireproof liquid used in combination. The fireproof putty includes: aggregate, biomass powder, graphite, toughening agent, methyl cellulose ether, nano silica, oxidized starch, and dipentaerythritol. The fireproof liquid includes: inorganic silicon flame retardant, waterproofing agent, wetting agent, dispersant, defoamer, and sodium methylsilicate.

[0004] However, the expansion layer is a loose and porous material that does not adhere tightly to the substrate. It is easy for it to crack, fall off on its own, or break under external force, thus exposing the steel to flames and causing it to lose its fireproof function.

[0005] To enhance the mechanical strength of the expansion layer, inorganic particles are currently mostly used as fillers, which play a supporting role in the expansion layer.

[0006] CN107083129A discloses a water-based ultra-thin fireproof coating for steel structures, which is made of the following components in weight percentage: 17-23.5% acetic acid emulsion, 18-25% MF resin-modified ammonium polyphosphate, 7-12% melamine, 7.5-12.5% ​​pentaerythritol, 0.8-1.5% film-forming aid, 0.20-0.50% defoamer, 0.30-0.60% dispersant, 0.10-0.30% preservative, 0.2-0.8% thickener, 4-8% titanium dioxide, 2-6% inorganic filler, 0.15-0.30% pH adjuster, and the balance being water.

[0007] However, micron-sized inorganic particles cannot effectively bond with the carbon layer formed during combustion, and the dispersed inorganic particles cannot form a continuous reinforcing phase, thus having a very limited effect on the expansion layer. They may even weaken the expansion effect of the expansion layer and lead to discontinuity and pulverization of the expansion layer.

[0008] Therefore, it is crucial to develop an intumescent fire-retardant coating that can overcome the above-mentioned defects. Summary of the Invention

[0009] To address the shortcomings of existing technologies, the present invention aims to provide an intumescent fire-retardant coating, its preparation method, and its application. The coating formed by the intumescent fire-retardant coating overcomes the problems of discontinuity in the expansion layer and reduced expansion effect caused by physical doping of inorganic particles, thereby achieving the effects of enhancing the mechanical strength of the expansion layer and enhancing thermal insulation protection.

[0010] To achieve this objective, the present invention adopts the following technical solution:

[0011] In a first aspect, the present invention provides an intumescent fire-retardant coating, the intumescent fire-retardant coating comprising an organosilicon-modified acrylic emulsion, a ceramic catalyst, an inorganic ceramic-forming functional filler, and an intumescent fire-retardant filler;

[0012] The organosilicon-modified acrylic emulsion comprises a host resin having a core-shell structure;

[0013] The core layer of the main resin contains acrylic monomers, styrene, and acrylate-based silicone oil.

[0014] The raw materials for the shell layer of the main resin include acrylic monomers and styrene.

[0015] In this invention, the intumescent fire-retardant coating combines an organosilicon-modified acrylic emulsion with a core-shell structure as the main resin, a ceramic catalyst, an inorganic ceramic-forming functional filler, and an intumescent fire-retardant filler. By utilizing in-situ enhancement technology for catalytic ceramicization, the resulting coating simultaneously forms a dense carbon layer and a molecular-level interpenetrating composite structure of high-strength ceramics during high-temperature combustion.

[0016] Specifically, under high-temperature fire conditions, the intumescent fire-retardant coating catalyzes the ceramic-forming reaction of organosilicon molecular chains in situ, resulting in a molecularly dispersed ceramic structure between the expanded carbon layers. The hard inorganic phase ceramic material and the soft carbon layer structure form an interpenetrating composite network. The ceramic catalyst can lower the ceramic-forming temperature of the organosilicon molecular chains and promote the ceramic-forming reaction. The inorganic ceramic-forming functional filler causes a eutectic ceramic-forming reaction with the silicon dioxide produced by the degradation of organosilicon. After the carbon layer expands, the organosilicon molecular chains undergo side chain decomposition, breakage, and re-crosslinking, forming a ceramic reinforcement together with other ceramic-forming functional materials. This overcomes the problem of discontinuity and reduced expansion effect caused by physical doping of inorganic particles, resulting in a higher mechanical strength and denser microporous structure in the expanded layer produced in high-temperature flames. This prevents the carbon layer from falling off and breaking, and enhances the thermal insulation protection performance of the expanded layer on the steel surface.

[0017] Preferably, the intumescent fire-retardant coating comprises the following components in parts by weight:

[0018]

[0019] In this invention, the reason for using each component in combination at specific amounts is that the synergistic effect of the components results in an intumescent fire-retardant coating with excellent overall performance. If the amount of ceramic catalyst added is too low, it will lead to a higher ceramicization temperature or failure to ceramicize; if the amount added is too high, it will lead to premature ceramicization and limit the expansion of the carbon layer. If the amount of inorganic ceramic-forming functional filler added is too low, it will lead to the inability to form an intumescent layer with mechanical strength; if the amount added is too high, it will affect the adhesion and expansion ratio of the coating. If the amount of intumescent fire-retardant filler added is too low, it will lead to a decrease in the expansion ratio of the coating; if the amount added is too high, it will lead to a decrease in the water resistance and adhesion of the coating.

[0020] In this invention, the organosilicon-modified acrylic emulsion is in the form of 12-22 parts by weight, such as 14 parts, 16 parts, 18 parts, 20 parts, etc.

[0021] The ceramicized catalyst is present in parts by weight of 0.5-2 parts, for example, 0.6 parts, 0.8 parts, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, etc.

[0022] The inorganic ceramic functional filler is 10-15 parts by weight, for example, 11 parts, 12 parts, 13 parts, 14 parts, etc.

[0023] The intumescent fireproof filler is 40-45 parts by weight, for example, 41 parts, 42 parts, 43 parts, 44 parts, etc.

[0024] Preferably, in the raw materials of the core layer of the main resin, the acrylic monomers include any one or a combination of at least two of methyl methacrylate, butyl acrylate, or methacrylic acid, wherein typical but non-limiting combinations include: a combination of methyl methacrylate and butyl acrylate, a combination of butyl acrylate and methacrylic acid, a combination of methyl methacrylate, butyl acrylate, and methacrylic acid, etc.

[0025] Preferably, the structure of the acrylate-based silicone oil is as shown in formula (1):

[0026]

[0027] Where m is an integer between 5 and 15, such as 6, 8, 10, 12, 14, etc.

[0028] Preferably, the acrylic monomer is in the range of 1-53 parts by weight, such as 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, etc.

[0029] Preferably, the methyl methacrylate is in the form of 10-30 parts by weight, such as 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, etc.

[0030] Preferably, the butyl acrylate is present in 10-20 parts by weight, such as 12 parts, 14 parts, 16 parts, or 18 parts.

[0031] Preferably, the methacrylic acid is in the form of 1-3 parts by weight, such as 0.2 parts, 0.4 parts, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, etc.

[0032] Preferably, the styrene is in the form of 1-10 parts by weight, such as 2 parts, 4 parts, 6 parts, 8 parts, etc.

[0033] Preferably, the acrylate-based silicone oil is present in 5-10 parts by weight, such as 6 parts, 7 parts, 8 parts, 9 parts, etc.

[0034] Preferably, in the raw materials of the shell layer of the main resin, the acrylic monomers include any one or a combination of at least two of methyl methacrylate, butyl acrylate, or methacrylic acid, wherein typical but non-limiting combinations include: a combination of methyl methacrylate and butyl acrylate, a combination of butyl acrylate and methacrylic acid, a combination of methyl methacrylate, butyl acrylate, and methacrylic acid, etc.

[0035] Preferably, the acrylic monomer is in the range of 1-50 parts by weight, such as 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, etc.

[0036] Preferably, the methyl methacrylate is present in 5-15 parts by weight, such as 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, etc.

[0037] Preferably, the butyl acrylate is present in 20-30 parts by weight, such as 22 parts, 24 parts, 26 parts, 28 parts, etc.

[0038] Preferably, the methacrylic acid is in the form of 1-5 parts by weight, such as 2 parts, 3 parts, 4 parts, etc.

[0039] Preferably, the styrene is in the form of 1-10 parts by weight, such as 2 parts, 4 parts, 6 parts, 8 parts, etc.

[0040] The reason for using the silicone-modified acrylic emulsion in this invention is that: although a partial ceramic reinforcement effect can be achieved by directly mixing silicone emulsion and acrylic emulsion using a physical method, the surface energy difference between silicone and acrylic is large, resulting in instability of the blended emulsion; furthermore, in the formed coating system, phase separation causes silicone molecules to easily migrate to the surface, and under the high temperature of the flame, the viscosity and fluidity of the surface resin are poor, resulting in sintering to form a hard shell, which cannot form a good expansion structure, affecting the final expansion ratio and fire resistance of the material.

[0041] Preferably, the ceramicized catalyst comprises any one or a combination of at least two of nano-cerium oxide, nano-iron oxide, or an aqueous solution of chloroplatinic acid, wherein typical but non-limiting combinations include: a combination of nano-cerium oxide and nano-iron oxide, a combination of nano-iron oxide and an aqueous solution of chloroplatinic acid, a combination of nano-cerium oxide, nano-iron oxide, and an aqueous solution of chloroplatinic acid, etc.

[0042] Preferably, the inorganic ceramic functional filler includes any one or a combination of at least two of titanium dioxide, mica powder, kaolin, diatomaceous earth, bentonite, silica powder, aluminum hydroxide, or boehmite. Typical but non-limiting combinations include: combinations of titanium dioxide, mica powder, and kaolin; combinations of diatomaceous earth, bentonite, silica powder, aluminum hydroxide, and boehmite; and combinations of titanium dioxide, mica powder, kaolin, diatomaceous earth, bentonite, silica powder, aluminum hydroxide, and boehmite.

[0043] Preferably, the intumescent fire-retardant filler includes a carbon donor, an acid donor, and a foaming agent.

[0044] Preferably, the carbon donor comprises pentaerythritol.

[0045] Preferably, the acid donor comprises ammonium polyphosphate.

[0046] Preferably, the foaming agent includes melamine.

[0047] Preferably, the mass ratio of the carbon donor, acid donor and foaming agent is (1-1.5):(2-3):1, wherein 1-1.5 can be 1.1, 1.2, 1.3, 1.4, etc.; and 2-3 can be 2.2, 2.4, 2.6, 2.8, etc.

[0048] In existing technologies, fiber materials are used to enhance the mechanical strength of the expanded carbon layer, but the effect is not obvious. Furthermore, the addition of too much inorganic filler will affect the coating's workability and expansion ratio, and increase the thermal conductivity of the expanded layer, which is not conducive to heat insulation and fireproofing.

[0049] Preferably, the intumescent fire-retardant coating further includes any one or a combination of at least two of the following: additives, fluxing agents, or a first solvent. Typical but non-limiting combinations include: a combination of additives and fluxing agents, a combination of fluxing agents and a first solvent, a combination of additives, fluxing agents, and a first solvent, etc.

[0050] Preferably, the additive includes any one or a combination of at least two of the following: dispersant, defoamer, thickener, film-forming aid, or pH adjuster. Typical but non-limiting combinations include: a combination of dispersant and defoamer; a combination of thickener, film-forming aid, and pH adjuster; a combination of defoamer, thickener, film-forming aid, and pH adjuster; and a combination of dispersant, defoamer, thickener, film-forming aid, and pH adjuster.

[0051] Preferably, the additive is present in 1-5 parts by weight, such as 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, etc.

[0052] Preferably, the flux comprises any one or a combination of at least two of sodium borate, potassium borate, or zinc borate, wherein typical but non-limiting combinations include: a combination of sodium borate and potassium borate, a combination of potassium borate and zinc borate, a combination of sodium borate, potassium borate, and zinc borate, etc.

[0053] In this invention, the flux acts as a binder and sintering aid, and lowers the ceramicization reaction temperature.

[0054] Preferably, the flux is 0.5-1 parts by weight, such as 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, etc.

[0055] Preferably, the first solvent includes water.

[0056] Preferably, the first solvent is 10-15 parts by weight, such as 11, 12, 13, or 14 parts.

[0057] In a second aspect, the present invention provides a method for preparing the intumescent fire-retardant coating described in the first aspect, the method comprising the following steps:

[0058] The intumescent fire-retardant coating is obtained by mixing organosilicon-modified acrylic emulsion, ceramic catalyst, inorganic ceramic functional filler and intumescent fire-retardant filler.

[0059] Preferably, the preparation method of the organosilicon-modified acrylic emulsion includes the following steps:

[0060] (1) A solution of acrylic monomers, styrene, acrylate silicone oil and emulsifier is mixed to obtain a pre-emulsion of the core layer;

[0061] A solution of acrylic monomers, styrene, and emulsifier is mixed to obtain a pre-emulsion for the shell layer;

[0062] (2) Mix the solution of the second solvent, emulsifier, buffer, initiator and part of the pre-emulsion of the core layer, and keep it warm to obtain the seed emulsion;

[0063] (3) Mix the seed emulsion, the remaining pre-emulsion of the nucleus layer and the initiator solution, keep warm and react to form the nucleus layer;

[0064] (4) Mix the material from step (3), the pre-emulsion of the shell layer, and the initiator solution, and keep it warm to form a shell layer to obtain the organosilicon-modified acrylic emulsion.

[0065] Preferably, in steps (1)-(2), the emulsifiers each independently comprise sodium dodecyl sulfate and / or dodecylphenol polyoxyethylene ether.

[0066] Preferably, when the emulsifier is a combination of sodium dodecyl sulfate and dodecylphenol polyoxyethylene ether, the mass ratio of the two is 1:(1-3), wherein 1-3 can be 1.5, 2, 2.5, etc.

[0067] Preferably, the buffer comprises slow-release sodium bicarbonate.

[0068] Preferably, in steps (2)-(4), the initiator includes ammonium persulfate.

[0069] Preferably, in step (2), the pre-emulsion of the partial core layer accounts for 2%-8% of the mass of the pre-emulsion of the entire core layer, such as 3%, 4%, 5%, 6%, 7%, etc.

[0070] Preferably, in step (2), the temperature of the heat preservation reaction is 70-90℃, such as 75℃, 80℃, 85℃, etc.

[0071] Preferably, the heat preservation reaction time is 10-50 min, such as 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, etc.

[0072] Preferably, in step (2), the mixing includes first mixing the second solvent, emulsifier and buffer, heating, then mixing with the initiator solution, and then adding a portion of the core layer pre-emulsion to the system.

[0073] Preferably, the temperature is raised to 70-80°C, such as 72°C, 74°C, 76°C, 78°C, etc.

[0074] Preferably, in step (3), the temperature of the heat preservation reaction is 70-90℃, such as 75℃, 80℃, 85℃, etc.

[0075] Preferably, the heat preservation reaction time is 10-50 min, such as 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, etc.

[0076] Preferably, in step (3), the mixing includes adding the pre-emulsion of the remaining core layer and the initiator solution dropwise to the system, respectively;

[0077] Preferably, in step (4), the temperature of the heat preservation reaction is 75-95℃ (e.g., 76℃, 78℃, 80℃, 82℃, 84℃, 86℃, 88℃, 90℃, 92℃, 94℃, etc.), which is higher than the temperature of the heat preservation reaction in step (3).

[0078] Preferably, the heat preservation reaction time is 40-80 min, such as 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, etc.

[0079] Preferably, in step (4), the mixing includes adding the pre-emulsion of the shell and the solution of the initiator to the system dropwise, respectively.

[0080] Preferably, the heat preservation reaction further includes cooling and pH adjustment.

[0081] Preferably, the pH is adjusted to 7.5-8.5, such as 7.6, 7.8, 8, 8.2, 8.4, etc.

[0082] As a preferred technical solution, the preparation method of the organosilicon-modified acrylic emulsion includes the following steps:

[0083] (1) A solution of acrylic monomers, styrene, acrylate silicone oil and emulsifier is mixed to obtain a pre-emulsion of the core layer;

[0084] A solution of acrylic monomers, styrene, and emulsifier is mixed to obtain a pre-emulsion for the shell layer;

[0085] (2) First, mix the second solvent, emulsifier and buffer, heat to 70-80℃, then mix with the initiator solution, then add part of the pre-emulsion of the core layer to the system, and keep the reaction at 70-90℃ for 10-50 min to obtain the seed emulsion;

[0086] (3) Add the remaining pre-emulsion of the core layer and the initiator solution dropwise to the system, and continue the reaction at the temperature for 10-50 min to form the core layer;

[0087] (4) The pre-emulsion of the shell and the solution of the initiator are added dropwise to the system, and the reaction is carried out at 75-95℃ for 40-80 min to form a shell. The temperature is then lowered and the pH is adjusted to 7.5-8.5 to obtain the organosilicon-modified acrylic emulsion.

[0088] Thirdly, the present invention provides an application of the intumescent fire-retardant coating described in the first aspect in steel materials.

[0089] Compared with the prior art, the present invention has the following beneficial effects:

[0090] (1) The coating formed by the intumescent fireproof coating of the present invention overcomes the problem of discontinuity of the expansion layer and reduced expansion effect caused by physical doping of inorganic particles, thereby achieving the effect of enhancing the mechanical strength of the expansion layer and enhancing heat insulation and protection.

[0091] (2) When the expansion ratio of the intumescent fireproof coating described in this invention is 30-36, the coating has good density, high strength, and fire resistance time of more than 45 minutes. Detailed Implementation

[0092] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0093] In this invention, the procurement information of some raw materials in each embodiment is as follows:

[0094] Dispersant: Polybasic acid copolymer, purchased from Guangzhou Yaxin New Materials Co., Ltd., brand name OROTAN 1124;

[0095] Defoamer: Organic modified polysiloxane emulsion, purchased from Shenzhen Dayang New Materials Co., Ltd., brand name BYK023;

[0096] Thickener: Hydroxyethyl cellulose, purchased from Feicheng Yutian Chemical Co., Ltd., brand name HEC 2500;

[0097] Film-forming aid: dipropylene glycol butyl ether, purchased from Guangzhou Yaxin New Materials Co., Ltd., brand name DPNB;

[0098] pH adjuster: 2-amino-2-methyl-1-propanol, purchased from Guangzhou Yaxin New Materials Co., Ltd., brand name AMP-95;

[0099] Acrylic silicone oil: purchased from Guangzhou Silok Polymer Co., Ltd., brand name Silok-3821F8;

[0100] Example 1

[0101] This embodiment provides an intumescent fire-retardant coating comprising the following components in parts by weight: 17 parts of silicone-modified acrylic emulsion, 1 part of ceramic catalyst, 12 parts of inorganic ceramic functional filler, 0.8 parts of flux, 42 parts of intumescent fire-retardant filler, 3 parts of additives, and 12 parts of water.

[0102] The ceramic catalyst consists of 0.5 parts of chloroplatinic acid aqueous solution (platinum content 5000ppm) and 0.5 parts of nano-cerium oxide; the inorganic ceramic functional filler consists of 5 parts of titanium dioxide, 5 parts of mica powder, and 2 parts of aluminum hydroxide; the flux is zinc borate; the intumescent fire-retardant filler consists of 20 parts of ammonium polyphosphate, 10 parts of melamine, and 12 parts of pentaerythritol; the additives include 1 part of dispersant, 0.3 parts of defoamer, 0.2 parts of thickener, 1 part of film-forming aid, and 0.5 parts of pH adjuster.

[0103] The intumescent fire-retardant coating is obtained by the following preparation method, which includes the following steps:

[0104] (1) Preparation of silicone-modified acrylic emulsion

[0105] 1) Monomer pre-emulsification: Take 1.5 parts of emulsifier (a mixture of sodium dodecyl sulfate and OP-10 in a mass ratio of 1:2) and 40 parts of deionized water, and stir at room temperature for 20 min; take 20 parts of methyl methacrylate, 5 parts of styrene, 15 parts of butyl acrylate, 1 part of methacrylic acid, and 8 parts of acrylate-based silicone oil, add them to the above emulsifier solution, and stir at high speed for 20 min to obtain the pre-emulsified solution of the core layer.

[0106] Weigh 1 part of emulsifier (a mixture of sodium dodecyl sulfate and OP-10 in a mass ratio of 1:2) and 45 parts of deionized water, and stir at room temperature for 20 min; weigh 10 parts of methyl methacrylate, 5 parts of styrene, 25 parts of butyl acrylate and 2 parts of methacrylic acid, add them to the above emulsifier solution, and stir at high speed for 20 min to obtain a pre-emulsion of the shell layer.

[0107] 2) Preparation of seed emulsion: Take 20 parts of deionized water, add 0.1 parts of buffer sodium bicarbonate, add 1 part of emulsifier, stir, slowly heat to 75°C, add 5 parts of 0.5% ammonium persulfate solution, add 5% of the above pre-emulsion of the core layer dropwise over 30 min, heat to 80°C, keep warm for 30 min, and obtain seed emulsion.

[0108] 3) Preparation of the core layer: The remaining pre-emulsion of the core layer and 10 parts of 0.5% ammonium persulfate solution were added dropwise evenly over 1 hour. The mixture was kept warm for 30 minutes to form the core layer.

[0109] 4) Preparation of the shell: The pre-emulsion of the shell and 10 parts of 0.5% ammonium persulfate solution were added dropwise evenly over 1 hour. The temperature was raised to 83°C and kept at that temperature for 1 hour to form the shell.

[0110] 5) Cool the system to 40°C and adjust the pH to 8 with ammonia to obtain the organosilicon-modified acrylic emulsion.

[0111] (2) Preparation of intumescent fire-retardant coatings

[0112] In a 100L container, deionized water was added, and the mixture was stirred at 500 rpm. Thickener, dispersant, and defoamer were added sequentially, and the mixture was stirred and dispersed for 5 minutes. Ceramic catalyst, inorganic ceramic functional filler, flux, and intumescent fire-retardant filler were added sequentially, and the stirring speed was increased to 1000 rpm, and the mixture was stirred and dispersed for 30 minutes. Organosilicon-modified acrylic emulsion, film-forming aid, defoamer, and pH adjuster were added sequentially, and the mixture was further dispersed at high speed for 20 minutes to obtain the intumescent fire-retardant coating.

[0113] Example 2-3

[0114] The difference between Examples 2-3 and Example 1 is that the amount of inorganic ceramic functional filler added is 8 parts (Example 2) and 18 parts (Example 3), respectively, and the mass ratio of titanium dioxide, mica powder and aluminum hydroxide is 5:3:2. All other aspects are the same as in Example 1.

[0115] Examples 4-5

[0116] The difference between Examples 4 and 5 and Example 1 is that the amount of ceramic catalyst added is 0.3 parts (Example 4) and 2.5 parts (Example 5), respectively, while the rest is the same as Example 1.

[0117] Examples 6-7

[0118] The difference between Examples 6 and 7 and Example 1 is that the amount of intumescent fire-retardant filler added is 38 parts (Example 6) and 50 parts (Example 7), respectively, and the mass ratio of ammonium polyphosphate, melamine and pentaerythritol is 23:10:12. All other aspects are the same as in Example 1.

[0119] Example 8

[0120] The difference between this embodiment and Embodiment 1 is that it does not include a flux; otherwise, they are the same as in Embodiment 1.

[0121] Example 9

[0122] This embodiment provides an intumescent fire-retardant coating comprising the following components in parts by weight: 12 parts of silicone-modified acrylic emulsion, 2 parts of ceramic catalyst, 15 parts of inorganic ceramic functional filler, 1 part of flux, 40 parts of intumescent fire-retardant filler, 1 part of additive, and 15 parts of water.

[0123] The ceramic catalyst consists of 1 part of chloroplatinic acid aqueous solution (platinum content 5000ppm) and 1 part of nano-cerium oxide; the inorganic ceramic functional filler consists of 5 parts of titanium dioxide, 5 parts of mica powder, and 5 parts of aluminum hydroxide; the flux is zinc borate; the intumescent fire-retardant filler consists of 23 parts of ammonium polyphosphate, 10 parts of melamine, and 12 parts of pentaerythritol; the additives include 0.3 parts of dispersant, 0.3 parts of defoamer, 0.2 parts of thickener, 0.1 parts of film-forming aid, and 0.1 parts of pH adjuster.

[0124] The intumescent fire-retardant coating is obtained by the following preparation method, which includes the following steps:

[0125] (1) Preparation of silicone-modified acrylic emulsion

[0126] Monomer pre-emulsification: Take 1.5 parts of emulsifier (a mixture of sodium dodecyl sulfate and OP-10 in a mass ratio of 1:2) and 40 parts of deionized water, and stir at room temperature for 20 min; take 20 parts of methyl methacrylate, 5 parts of styrene, 15 parts of butyl acrylate, 1 part of methacrylic acid, and 8 parts of acrylate-based silicone oil, add them to the above emulsifier solution, and stir at high speed for 20 min to obtain the pre-emulsified solution of the core layer.

[0127] Weigh 1 part of emulsifier (a mixture of sodium dodecyl sulfate and OP-10 in a mass ratio of 1:2) and 45 parts of deionized water, and stir at room temperature for 20 min; weigh 10 parts of methyl methacrylate, 5 parts of styrene, 25 parts of butyl acrylate and 2 parts of methacrylic acid, add them to the above emulsifier solution, and stir at high speed for 20 min to obtain a pre-emulsion of the shell layer.

[0128] 2) Preparation of seed emulsion: Take 20 parts of deionized water, add 0.1 parts of buffer sodium bicarbonate, add 1 part of emulsifier, stir, slowly heat to 75°C, add 5 parts of 0.5% ammonium persulfate solution, add 5% of the above pre-emulsion of the core layer dropwise over 30 min, heat to 80°C, keep warm for 30 min, and obtain seed emulsion.

[0129] 3) Preparation of the core layer: The remaining pre-emulsion of the core layer and 10 parts of 0.5% ammonium persulfate solution were added dropwise evenly over 1 hour. The mixture was kept warm for 30 minutes to form the core layer.

[0130] 4) Preparation of the shell: The pre-emulsion of the shell and 10 parts of 0.5% ammonium persulfate solution were added dropwise evenly over 1 hour. The temperature was raised to 83°C and kept at that temperature for 1 hour to form the shell.

[0131] 5) Cool the system to 40°C and adjust the pH to 8 with ammonia to obtain the organosilicon-modified acrylic emulsion.

[0132] (2) Preparation of intumescent fire-retardant coatings

[0133] In a 100L container, deionized water was added, and the mixture was stirred at 500 rpm. Thickener, dispersant, and defoamer were added sequentially, and the mixture was stirred and dispersed for 5 minutes. Ceramic catalyst, inorganic ceramic functional filler, flux, and intumescent fire-retardant filler were added sequentially, and the stirring speed was increased to 1000 rpm, and the mixture was stirred and dispersed for 30 minutes. Organosilicon-modified acrylic emulsion, film-forming aid, defoamer, and pH adjuster were added sequentially, and the mixture was further dispersed at high speed for 20 minutes to obtain the intumescent fire-retardant coating.

[0134] Example 10

[0135] This embodiment provides an intumescent fire-retardant coating comprising the following components in parts by weight: 22 parts of silicone-modified acrylic emulsion, 0.5 parts of ceramic catalyst, 10 parts of inorganic ceramic functional filler, 0.5 parts of flux, 45 parts of intumescent fire-retardant filler, 5 parts of additives, and 10 parts of water.

[0136] The ceramic catalyst consists of 0.25 parts of chloroplatinic acid aqueous solution (platinum content 5000ppm) and 0.25 parts of nano-cerium oxide; the inorganic ceramic functional filler consists of 5 parts of titanium dioxide, 3 parts of mica powder, and 2 parts of aluminum hydroxide; the flux is zinc borate; the intumescent fire-retardant filler consists of 20 parts of ammonium polyphosphate, 10 parts of melamine, and 10 parts of pentaerythritol; the additives include 1 part of dispersant, 1 part of defoamer, 1 part of thickener, 1 part of film-forming aid, and 1 part of pH adjuster.

[0137] The intumescent fire-retardant coating is obtained by the following preparation method, which includes the following steps:

[0138] (1) Preparation of silicone-modified acrylic emulsion

[0139] Monomer pre-emulsification: Take 1.5 parts of emulsifier (a mixture of sodium dodecyl sulfate and OP-10 in a mass ratio of 1:2) and 40 parts of deionized water, and stir at room temperature for 20 min; take 20 parts of methyl methacrylate, 5 parts of styrene, 15 parts of butyl acrylate, 1 part of methacrylic acid, and 8 parts of acrylate-based silicone oil, add them to the above emulsifier solution, and stir at high speed for 20 min to obtain the pre-emulsified solution of the core layer.

[0140] Weigh 1 part of emulsifier (a mixture of sodium dodecyl sulfate and OP-10 in a mass ratio of 1:2) and 45 parts of deionized water, and stir at room temperature for 20 min; weigh 10 parts of methyl methacrylate, 5 parts of styrene, 25 parts of butyl acrylate and 2 parts of methacrylic acid, add them to the above emulsifier solution, and stir at high speed for 20 min to obtain a pre-emulsion of the shell layer.

[0141] 2) Preparation of seed emulsion: Take 20 parts of deionized water, add 0.1 parts of buffer sodium bicarbonate, add 1 part of emulsifier, stir, slowly heat to 75°C, add 5 parts of 0.5% ammonium persulfate solution, add 5% of the above pre-emulsion of the core layer dropwise over 30 min, heat to 80°C, keep warm for 30 min, and obtain seed emulsion.

[0142] 3) Preparation of the core layer: The remaining pre-emulsion of the core layer and 10 parts of 0.5% ammonium persulfate solution were added dropwise evenly over 1 hour. The mixture was kept warm for 30 minutes to form the core layer.

[0143] 4) Preparation of the shell: The pre-emulsion of the shell and 10 parts of 0.5% ammonium persulfate solution were added dropwise evenly over 1 hour. The temperature was raised to 83°C and kept at that temperature for 1 hour to form the shell.

[0144] 5) Cool the system to 40°C and adjust the pH to 8 with ammonia to obtain the organosilicon-modified acrylic emulsion.

[0145] (2) Preparation of intumescent fire-retardant coatings

[0146] In a 100L container, deionized water was added, and the mixture was stirred at 500 rpm. Thickener, dispersant, and defoamer were added sequentially, and the mixture was stirred and dispersed for 5 minutes. Ceramic catalyst, inorganic ceramic functional filler, flux, and intumescent fire-retardant filler were added sequentially, and the stirring speed was increased to 1000 rpm, and the mixture was stirred and dispersed for 30 minutes. Organosilicon-modified acrylic emulsion, film-forming aid, defoamer, and pH adjuster were added sequentially, and the mixture was further dispersed at high speed for 20 minutes to obtain the intumescent fire-retardant coating.

[0147] Comparative Example 1

[0148] This comparative example provides an intumescent fire retardant coating, which was purchased from Weicheng Fire Protection Technology Group Co., Ltd., with the brand name GT-NSP-Fp1.00-HBCD.

[0149] Comparative Example 2

[0150] The difference between this comparative example and Example 1 is that it does not include a ceramic catalyst; otherwise, they are the same as in Example 1.

[0151] Comparative Example 3

[0152] The difference between this comparative example and Example 1 is that the silicone-modified acrylic emulsion does not include a shell layer, and the preparation method does not include a pre-emulsion with a shell layer or the preparation of the shell layer. All other aspects are the same as in Example 1.

[0153] Comparative Example 4

[0154] The difference between this comparative example and Example 1 is that the organosilicon-modified acrylic emulsion does not include the core layer. The preparation method directly uses the pre-emulsion of the shell layer to prepare the seed emulsion and carry out the next growth step. All other aspects are the same as in Example 1.

[0155] Performance testing

[0156] The intumescent fire-retardant coatings described in Examples 1-10 and Comparative Examples 1-4 were tested as follows:

[0157] (1) Strength test of expansion layer: 80mm×40mm×1.2mm steel was selected. After sanding and cleaning, the expansion-type fireproof coating was applied to the steel, and the dry film thickness was controlled at (1±0.1)mm. The coating was tested with a gasoline torch for 1 hour. After the experiment was stopped, the expanded coating was blown from a distance of 30cm from the front using a blower at different speeds. The carbon layer strength was defined according to the wind speed at different speeds and the degree of damage to the carbon layer after the test, and was represented by numbers 1-10, where 1 represents the weakest strength and 10 represents the best strength.

[0158] (2) Fire resistance time test: Select 80mm×40mm×1.2mm steel, sand it and clean it, then apply intumescent fire retardant coating to the steel, controlling the dry film thickness to be (1±0.1)mm. Use a rapid fire resistance performance testing device to test the fire resistance performance, and take the time for the back temperature of the steel to reach 538℃ as the fire resistance time.

[0159] (3) Expansion ratio: Select 80mm×40mm×1.2mm steel, sand and clean it, then apply the intumescent fire retardant coating to the steel, controlling the dry film thickness to be (1±0.1)mm. Use a gasoline torch to ignite and test for 1 hour. After stopping the experiment, measure the expansion height of the coating and divide it by the initial dry film thickness to obtain the expansion ratio.

[0160] (4) Density of the expansion layer: 80mm×40mm×1.2mm steel was selected. After sanding and cleaning, the intumescent fire-retardant coating was applied to the steel, controlling the dry film thickness to be (1±0.1)mm. A gasoline torch was used for ignition testing for 1 hour. After the experiment, the expanded coating was longitudinally cut with a utility knife, and the density of the expansion layer on the cross-section was observed visually. The density decreased in the following order: dense > relatively dense > relatively loose > loose. The criteria for judgment were: dense, on the cross-section, the area of ​​voids >1mm was less than or equal to 5% of the total cross-sectional area; relatively dense, on the cross-section, the area of ​​voids >1mm accounted for 5%-10% (inclusive) of the total cross-sectional area; relatively loose, on the cross-section, the area of ​​voids >1mm accounted for 10%-20% (inclusive) of the total cross-sectional area; loose, on the cross-section, the area of ​​voids >1mm was greater than 20% of the total cross-sectional area.

[0161] The test results are summarized in Table 1.

[0162] Table 1

[0163]

[0164]

[0165] Analysis of the data in Table 1 shows that the intumescent fireproof coating of the present invention forms a coating with an expansion ratio of 30-36, good density of the expansion layer, high strength of the expansion layer, and a fire resistance time of more than 45 minutes. The intumescent fireproof coating of the present invention overcomes the problem of discontinuity of the expansion layer and reduced expansion effect caused by physical doping of inorganic particles, thereby achieving the effect of enhancing the mechanical strength of the expansion layer and enhancing heat insulation and protection.

[0166] Analysis of Comparative Example 1 and Example 1 shows that the performance of Comparative Example 1 is not as good as that of Example 1, proving that the intumescent fire-retardant coating of the present invention has better performance.

[0167] Analysis of Comparative Example 2 and Example 1 shows that the performance of Comparative Example 2 is not as good as that of Example 1, proving that the intumescent fire retardant coating formed by the ceramic catalyst has better performance.

[0168] Analysis of Comparative Examples 3-4 and Example 1 shows that the performance of Comparative Examples 3-4 is not as good as that of Example 1, proving that the intumescent fire retardant coating formed by using an organosilicon-modified acrylic emulsion with a core-shell structure as the main resin has better performance.

[0169] Analysis of Examples 2-3 and Example 1 shows that the performance of Examples 2-3 is not as good as that of Example 1, proving that the intumescent fireproof coating formed by adding inorganic ceramic functional fillers in the range of 10-15 parts has better performance.

[0170] Analysis of Examples 4-5 and Example 1 shows that the performance of Examples 4-5 is not as good as that of Example 1, proving that the intumescent fire retardant coating formed when the amount of ceramic catalyst added is in the range of 0.5-2 parts has better performance.

[0171] Analysis of Examples 6-7 and Example 1 shows that the performance of Examples 6-7 is not as good as that of Example 1, proving that the intumescent fire-retardant coating formed when the amount of intumescent fire-retardant filler added is in the range of 40-45 parts has better performance.

[0172] Analysis of Example 8 and Example 1 shows that the performance of Example 8 is not as good as that of Example 1, proving that the intumescent fire retardant coating formed by adding flux has better performance.

[0173] The present invention has been illustrated with the above embodiments to explain the detailed method of the present invention. However, the present invention is not limited to the detailed method described above, that is, it does not mean that the present invention must rely on the detailed method described above to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An intumescent fire-retardant coating, characterized in that, The intumescent fire-retardant coating includes an organosilicon-modified acrylic emulsion, a ceramic catalyst, an inorganic ceramic-forming functional filler, and an intumescent fire-retardant filler. The organosilicon-modified acrylic emulsion comprises a host resin having a core-shell structure; The core layer of the main resin contains acrylic monomers, styrene, and acrylate-based silicone oil. The raw materials for the shell layer of the main resin include acrylic monomers and styrene; The ceramicized catalyst includes any one or a combination of at least two of nano-cerium oxide, nano-iron oxide, or an aqueous solution of chloroplatinic acid. The inorganic ceramic functional filler includes any one or a combination of at least two of the following: titanium dioxide, mica powder, kaolin, diatomaceous earth, bentonite, silica powder, aluminum hydroxide, or boehmite. The intumescent fire-retardant filler includes a carbon donor, an acid donor, and a foaming agent; The carbon donor includes pentaerythritol; The acid donor includes ammonium polyphosphate; The foaming agent includes melamine.

2. The intumescent fire-retardant coating according to claim 1, characterized in that, The intumescent fire-retardant coating comprises the following components in parts by weight: 12-22 parts of silicone-modified acrylic emulsion 0.5-2 parts of ceramicized catalyst 10-15 parts of inorganic ceramic functional filler 40-45 parts of intumescent fireproof filler.

3. The intumescent fire-retardant coating according to claim 1, characterized in that, In the raw materials of the core layer of the main resin, the acrylic monomers include any one or a combination of at least two of methyl methacrylate, butyl acrylate, or methacrylic acid.

4. The intumescent fire-retardant coating according to claim 1, characterized in that, The structure of the acrylate-based silicone oil is shown in formula (1): Equation (1); Where m is an integer between 5 and 15.

5. The intumescent fire-retardant coating according to claim 1, characterized in that, In the raw materials of the core layer of the main resin, the acrylic monomers are 1-53 parts by weight, the styrene is 1-10 parts by weight, and the acrylate-based silicone oil is 5-10 parts by weight.

6. The intumescent fire-retardant coating according to claim 1, characterized in that, In the raw materials of the shell layer of the main resin, the acrylic monomers include any one or a combination of at least two of methyl methacrylate, butyl acrylate, or methacrylic acid.

7. The intumescent fire-retardant coating according to claim 1, characterized in that, In the raw materials of the shell layer of the main resin, the acrylic monomers are 1-50 parts by weight and the styrene is 1-10 parts by weight.

8. The intumescent fire-retardant coating according to claim 1, characterized in that, The mass ratio of the carbon donor, acid donor, and foaming agent is (1-1.5):(2-3):

1.

9. The intumescent fire-retardant coating according to claim 2, characterized in that, The intumescent fire-retardant coating also includes any one or a combination of at least two of the following: additives, fluxing agents, or a first solvent.

10. The intumescent fire-retardant coating according to claim 9, characterized in that, The additives include any one or a combination of at least two of the following: dispersants, defoamers, thickeners, film-forming aids, or pH adjusters.

11. The intumescent fire-retardant coating according to claim 9, characterized in that, The amount of the auxiliary agent is 1-5 parts by weight.

12. The intumescent fire-retardant coating according to claim 9, characterized in that, The flux includes any one or a combination of at least two of sodium borate, potassium borate, or zinc borate.

13. The intumescent fire-retardant coating according to claim 9, characterized in that, The flux is present in 0.5-1 parts by weight.

14. The intumescent fire-retardant coating according to claim 9, characterized in that, The first solvent includes water.

15. The intumescent fire-retardant coating according to claim 9, characterized in that, The first solvent is 10-15 parts by weight.

16. A method for preparing an intumescent fire-retardant coating according to any one of claims 1-8, characterized in that, The preparation method includes the following steps: The intumescent fire-retardant coating is obtained by mixing organosilicon-modified acrylic emulsion, ceramic catalyst, inorganic ceramic functional filler and intumescent fire-retardant filler.

17. The preparation method according to claim 16, characterized in that, The preparation method of the organosilicon-modified acrylic emulsion includes the following steps: (1) A solution of acrylic monomers, styrene, acrylate silicone oil and emulsifier is mixed to obtain a pre-emulsion of the core layer; A solution of acrylic monomers, styrene, and emulsifier is mixed to obtain a pre-emulsion for the shell layer; (2) Mix the solution of the second solvent, emulsifier, buffer, initiator and part of the pre-emulsion of the core layer, and keep it warm to obtain the seed emulsion; (3) Mix the seed emulsion, the remaining pre-emulsion of the nucleus layer and the initiator solution, and keep the mixture warm to form the nucleus layer; (4) Mix the material from step (3), the pre-emulsion of the shell layer and the initiator solution, and keep it at a constant temperature to form a shell layer, thereby obtaining the organosilicon-modified acrylic emulsion.

18. The preparation method according to claim 17, characterized in that, In steps (1)-(2), each of the emulsifiers independently comprises sodium dodecyl sulfate and / or dodecylphenol polyoxyethylene ether.

19. The preparation method according to claim 18, characterized in that, When the emulsifier is a combination of sodium dodecyl sulfate and dodecylphenol polyoxyethylene ether, the mass ratio of the two is 1:(1-3).

20. The preparation method according to claim 17, characterized in that, The buffer includes sodium bicarbonate.

21. The preparation method according to claim 17, characterized in that, In steps (2)-(4), the initiator includes ammonium persulfate.

22. The preparation method according to claim 17, characterized in that, In step (2), the pre-emulsion of the partial core layer accounts for 2%-8% of the total mass of the pre-emulsion of the entire core layer.

23. The preparation method according to claim 17, characterized in that, In step (2), the temperature of the heat preservation reaction is 70-90℃.

24. The preparation method according to claim 17, characterized in that, In step (2), the heat preservation reaction time is 10-50 min.

25. The preparation method according to claim 17, characterized in that, In step (2), the mixing includes first mixing the second solvent, emulsifier and buffer, heating, then mixing with the initiator solution, and then adding a portion of the core layer pre-emulsion to the system.

26. The preparation method according to claim 25, characterized in that, The temperature is raised to 70-80℃.

27. The preparation method according to claim 17, characterized in that, In step (3), the temperature of the heat preservation reaction is 70-90℃.

28. The preparation method according to claim 17, characterized in that, In step (3), the heat preservation reaction time is 10-50 min.

29. The preparation method according to claim 17, characterized in that, In step (3), the mixing includes adding the remaining core layer pre-emulsion and the initiator solution to the system dropwise.

30. The preparation method according to claim 17, characterized in that, In step (4), the temperature of the heat preservation reaction is 75-95℃, which is higher than the temperature of the heat preservation reaction in step (3).

31. The preparation method according to claim 17, characterized in that, In step (4), the heat preservation reaction time is 40-80 min.

32. The preparation method according to claim 17, characterized in that, In step (4), the mixing includes adding the pre-emulsion of the shell and the solution of the initiator to the system dropwise.

33. The preparation method according to claim 17, characterized in that, In step (4), the heat preservation reaction is followed by cooling and pH adjustment.

34. The preparation method according to claim 33, characterized in that, The pH is adjusted to 7.5-8.

5.

35. The application of an intumescent fire-retardant coating according to any one of claims 1-15 in steel materials.

Citation Information

Patent Citations

  • Waterborne ultrathin steel structure fireproof coating material and preparation method thereof

    CN107083129A

  • Waterborne thin-steel-structure fireproof coating and fireproof mud and preparation method thereof

    CN108410352A

  • Nuclear-grade high-temperature-resistance fireproof coating and preparation method thereof

    CN104726020A

  • Aerogel-containing water-based expansion type fire-retardant coating and preparation method thereof

    CN106479297A